Antifungal activity of Boesenbergia rotunda (temukunci) extract against filamentous spoilage fungi from vegetables - Zakuan, Zulfa; Mustapa, S. A.; Sukor, Rashidah; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
The filamentous spoilage fungi in vegetables can lead to significant impact in food and economic loss. In order to overcome this problem, chemical fungicide has been implemented in vegetable farming and processing but it causes problems towards environment and food safety. Thus, the utilization of natural products such as plants extracts, which exhibit antimicrobial and antifungal activity, is more acceptable to solve this problem. The aim of this study is to investigate the antifungal activity of Boesenbergia rotunda extract against ten filamentous spoilage fungi isolated from five vegetables. The extract was used to treat fungal isolates from vegetables; CRb 002 (Penicillium sp.), CHa 009 (Aspergillus sp.), TMa 001 (Geotrichum sp.), TMa 002 (Aspergillus sp), ONb 001 (Aspergillus sp.), WBb 003 and WBb 004 (Fusarium sp.) WBb 007 (unidentified), WBb 008 (Aureobasidium sp.) and WBb 010 (Penicillium sp.). The results showed that the yield of the extract of B. rotunda using ethanol (95%) was 11.42% (w/v). The 10% of B. rotunda extract exhibited antifungal activities against ten filamentous fungi after 5 days treatment with growth reduction of 41.56%, 30.68%, 86.20%, 50.62%, 26.67%, 47.44%, 50.74%, 36.39%, 42.86%, and 39.39% for WBb 008, WBb 004, WBb 007, WBb 003, CRb 002, WBb 010, CHa 009, TMa 001, ONb 001, and TMa 002, respectively. B. rotunda extract showed highest antifungal activity against fungi isolated from winged bean (WBb 007) with percentage reduction in growth was 86.20%, while the lowest activity was against fungi isolated from the carrot (CRb 002) with 26.67% reduction in growth. Generally, the TPC of fungi in the vegetable samples were reduced after treatment with 5% of B. rotunda extract at 5 min and 10 min of exposure time. The results suggested that B. rotunda extract has high potential to become natural food preservative which can reduce the fungi spoilage of vegetables.